Recruiting business expatriates in Portugal: The moderating role of employee willingness - Coelho, J. V. (2022)
The present study examines the practices that multinational companies located in a small, open and peripheral European economy (Portugal) are acting to build talent pools for expatriate assignments. The role of employee willingness (to go) is explored as a dimension influencing the existing firm staffing practices’ success. By using a Portuguese sample, the study examines whether prior findings in mature economies and consolidated multinational companies can be generalised to peripheral and less-developed international business settings. Five business contexts and 24 expatriate cases were considered to ground empirical analysis. The prevalence of internal recruitment practices, informal and closed systems and staffing criteria, and less established international mobility and staffing experience, suggest the existence of critical differences with the current best-of-breed practices. Study findings indicate that divergent willingness profiles operate as moderating factors of firm propensity to use international work to support expansion goals. A typology of business expatriate willingness profiles (conformist expatriates, trajectory-focused expatriates and disrupted expatriates) is proposed to showcase expatriation assignments as a contemporary socioeconomic heterogenetic condition.